UANG DAN KEBIJAKAN MONETER DALAM PERSPEKTIF EKONOMI ISLAM - Rahmawati, Anita (EQUILIBRIUM, 2013)
This paper describes the concept and functions of money in the Islamic economics perspective and analyze the role of money in monetary policy in Islam. The review was interesting to be discussed because there are fundamental differences between the concepts and functions of money in the modern economy and Islamic economics perspectives. In Islam, money is a flow concept and public goods, while capital is a stock concept and private goods. Instead, the concept of money in a modern economy is often interpreted as interchangeability that money as money and money as capital. The presence of money in the economic system will affect the economy of a country, which is usually associated with monetary policy. However, differences in the prevailing economic system, would have a different view about money and monetary policy.